The influence of democratic leadership style, training, compensation, on athletes' performance in improving futsal achievement in Bekasi City - Aprizal, Ananda; Pragiwani, Meita; H.R, Imron (Indonesian Journal of Business, Accounting and Management, 2023)
This study aims to analyze the influence of democratic leadership style, training, and compensation variables on athletes' performance in enhancing futsal achievement. The research employs a quantitative approach, with data collection conducted through questionnaires with a sample of 75 futsal athletes from Bekasi City. The research method utilizes the path analysis model to represent latent variables. The stages of PLS analysis in this study include outer model analysis, inner model analysis, and hypothesis testing. The results of this study indicate that democratic leadership style, training, and compensation significantly influence athletes' performance in enhancing futsal achievement in Bekasi City. Note: This article serves as a restored version of the original content following a corruption incident. The Digital Object Identifier (DOI) has been successfully re-registered and reactivated to ensure continued accessibility and citation integrity.